Effect of contrast agent viscosity and massage on success of computed tomography lymphangiography with aqueous contrast for sentinel lymph node identification in healthy dogs. (27th April 2021) - Grimes, Janet A.; Reed, Rachel A.; Beale, Chelsea; Secrest, Scott A.
Abstract: Sentinel lymph node (SLN) evaluation is important for accurate cancer staging. Computed tomography (CT) lymphangiography with aqueous contrast is a feasible technique for SLN identification in dogs. Although most studies report success rates around 90%, success rates as low as 60% have been reported. One reason for low success rates may be the difference in viscosity of the various agents used in comparison to normal lymph viscosity. The objective of this study was to evaluate contrast agents of differing viscosities for use in CT lymphangiography for SLN identification and to determine the influence of massage on contrast flow rates. The hypothesis was that lower viscosity agents would have a higher success rate and faster time to identification of the SLN than higher viscosity agents and that massage would increase contrast flow rates. Dogs were anaesthetised and CT lymphangiography was performed with four contrast agents of differing viscosities in a randomized crossover design. Injections were made on the dorsal pes bilaterally on two study days and the popliteal lymph nodes were evaluated for contrast uptake. There was no significant difference in success of SLN identification or time to SLN identification among the four agents. Massage of the injection site increased rate of contrast flow through the lymphatics. No specific recommendation for one contrast agent over another can be made with these results. Massage is recommended to improve lymphatic flow when performing CT lymphangiography with aqueous contrast in dogs.